PubsMeetT1: A guide for enhancing tertiary ESL speaking skills - Joseph A. Alagiaraj Thambu Raj; Asmaa Abdulhameed Mohammad Al-saqqaf; Lindey Easter Apolonius (Pasir Mas Kelantan: Academica Press Solution, 2022)
Many Malaysian ESL undergraduates encounter communication apprehension while performing public speaking activities as they continue learning their respective courses that require oral presentations as part of assessments through online platforms as well as face to face classes. Accordingly, courses need to be tweaked to cater for the demand of crucial employability skill which requires the individual to have communication skills and to be a fluent English speaker. Realizing that many Malaysian ESL undergraduates experience communication apprehension when it comes to public speaking or oral presentation skills which impedes employability, thus, an effective and engaging technique needs to be implemented in a way that can incorporate speaking skills through the usage of the target language. An interactive meeting template known as Public Speaking Meeting Template 1 (PubsMeetT 1), has been developed for ESL teaching and learning to enhance the oral presentation skills among the undergraduates. This template would be a guide to enhance the undergraduates’ oral presentation skills as it will involve the ESL learners to take part in specific roles for classes based on the roles assigned. Thus, the objective of the template is to prepare ESL undergraduates for real-life meetings that need different responses at times and to create a conducive environment to promote communication and leadership skills at meetings. The novelty of this template is that it is designed for an hour’s session that could be utilized conveniently for different classes as it can be re-used by editing the interactive template that caters for the needs of the course which promotes a positive environment to foster communication skills.